Conn's current theraphy 2013 - Conn, Howard F. (Howard Franklin) 1908-1982; Bope, Edward T.; Kellerman, Rick D. (Elsevier Saunders, 2013)
Ideal for busy medical practitioners who need quick, reliable answers, Conn's Current Therapy is the one resource that focuses solely on the most up-to-date treatment protocols for the most common complaints and diagnoses. Hundreds of international contributors provide evidence-based advice to help you make more effective diagnoses and apply the most promising therapeutic strategies.